Chemical weathering intensity and geochemical characteristics of Cretaceous terrigenous clastic rock‐purple soil profiles in the Pushi area, Xichang. Issue 9 (11th July 2022) - Li, Tong; Li, Youguo; Liu, Hong; Li, Suimin; Ouyang, Yuan; Li, Chang; Zhang, Kai; Li, Jia; Zhang, Jinghua; Zhang, Tengjiao; Huang, Yong; Wu, Junyi
Abstract : The Pushi area of South‐west China features a large area of purple soil that formed by the weathering of Cretaceous terrigenous clastic rocks. In this study, four vertical profiles of the purple soil (P1, P2, P3, and P4) derived from different pedogenic parent rocks were investigated. Specifically, the chemical weathering intensity and element migration, enrichment, and differentiation characteristics were analysed and the influencing factors of chemical weathering were explored. According to the discrimination map of major and trace elements and content characteristics of rare earth elements, the soil profiles are controlled by complex chemical weathering processes. Various geochemical parameters and indicators exhibited good correlation, and the chemical weathering intensity of the profiles followed the order P1 (mudstone) > P3 (silty mudstone) > P4 (argillaceous siltstone) > P2 (sandstone). The overall chemical weathering intensity of argillaceous rocks was slightly higher than that of sandstone, and the four profiles generally reflected medium to strong chemical weathering. The migration, enrichment, and differentiation characteristics of geochemical elements were found to be mainly affected by different chemical weathering intensities and stages, followed by leaching deposition. The chemical weathering characteristics varied for the four profiles with different pedogenic parent rocks, which could be mainly attributed to internal factors such as the lithology of the pedogenic parent rock and external topographic factors such as altitude. Abstract : The Pushi area of South‐west China features a large area of purple soil that formed by the weathering of Cretaceous terrigenous clastic rocks. The overall chemical weathering intensity of argillaceous rocks was slightly higher than that of sandstone, and the four profiles generally reflected medium to strong chemical weathering. The chemical weathering characteristics varied for the four profiles with different pedogenic parent rocks, which could be mainly attributed to internal factors such as the lithology of the pedogenic parent rock and external topographic factors such as altitude.